An updated review of lipid‐modifying therapy. Issue 2 (21st April 2019) - Simons, Leon A
Summary: Statin drugs reduce low‐density lipoprotein (LDL)‐cholesterol (LDL‐C) and cardiovascular risk. Ezetimibe may be used to supplement statin therapy, or used alone in cases of statin intolerance. Statin‐associated side effects do occur, especially muscle symptoms and new onset diabetes, but they do not detract from the benefits of statin therapy. Inhibitors of proprotein convertase subtilisin/kexin type 9 (PCSK9) reduce LDL‐C and cardiovascular risk. Evolocumab is subsidised in Australia for patients with familial hypercholesterolaemia when LDL‐C is not adequately controlled with maximum doses of statin or ezetimibe or when statin therapy is contraindicated. Fenofibrate reduces triglycerides and cardiovascular risk in patients with type 2 diabetes when triglycerides are elevated and high‐density lipoprotein (HDL) is low. A role for dietary omega‐3 fatty acids and esters in reducing cardiovascular risk remains controversial. All cases of secondary cardiovascular disease prevention merit intensive lipid therapy, unless a contraindication exists. Lipid therapy is justified in cases of primary prevention when absolute risk is high, especially when lipids are highly elevated or when multiple risk factors are present. Clinical management requires a focus on the predominant lipid disorder present, namely hypercholesterolaemia, hypertriglyceridaemia or combined hyperlipidaemia. There is an ongoing problem of poor long term persistence on lipid therapy, as well as reduced awareness by practitioners of poor risk factor control.